The Effect of Financial Accounting Training on Student Performance with Academic Self-Efficacy as A Mediation - Rani Kharisma Haq; I Made Narsa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Academic performance becomes an important thing for students to measure theri learning outcomes. In addition to getting on-campus, many students also take a training as a support. This research aims to test the directly and indirect influence of financial accounting training mediated by academic self-efficacy on student academic performance. Whether by following the training or course in accounting, students have a better self-efficacy, as we know the advantages of training is to develop a knowledges and skills. The study also answered whether Self-efficacy obtained by students can affect academic performance as measured by their GPA. The sample used is an active undergraduate student in Accounting at Airlangga university. This research is quantitative research using primary data in the form of questionnaires. Data collection techniques using sample random sampling with the testing method used are regression analysis test and Sobel test. Test results based on questionnaires collected showed that students who had attended financial accounting training tended to obtain a better performance index. Then, the academic self-efficacy in students who have attended financial accounting training can be a variable that supports students to obtain a better performance index. Thus, this variable is able to mediate the relationship between financial accounting training and academic performance obtained by students. In addition, this study tries to fill the research gap.